ISLAM E MÍDIA: UM DIÁLOGO POSSÍVEL? - HAMMADEH, JIHAD HASSAN (2019)
This work aims to understand how Islam and Muslims were portrayed in Veja magazine during the year 2016. We hypothesize that, from a bias that relates the Islamic religion and its practitioners to terrorism and acts of violence, the representations in the news media, especially in Veja magazine, are mostly negative. Using theoretical references from the studies on Islam, we conducted a content analysis to categorize the reports that are part of our sample for accessibility in: contents related to violence; not related to violence and those that do not approach the religious theme. We obtained in our results the proof of the initial hypothesis, since in the majority of the journalistic contents connected to Islam and the Muslims were found more elements that related them to the violence to the terrorism of general way, than its simple presentation like religious.